2022
DOI: 10.1093/sleep/zsac155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of auditory sleep modulation approaches on brain oscillatory and cardiovascular dynamics

Abstract: Slow waves, the hallmark feature of deep nonrapid eye movement sleep, do potentially drive restorative effects of sleep on brain and body functions. Sleep modulation techniques to elucidate the functional role of slow waves thus have gained large interest. Auditory slow wave stimulation is a promising tool; however, directly comparing auditory stimulation approaches within a night and analyzing induced dynamic brain and cardiovascular effects are yet missing. Here, we tested various auditory stimulation approa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 80 publications
3
15
0
Order By: Relevance
“…Perhaps this rhythm entrained EEG oscillations in some participants, influencing slow-oscillation phase and delta power changes. Indeed, a recent study suggests that openloop auditory stimulation can induce slow-oscillation amplitude changes (Huwiler et al, 2022). Batterink et al (2016) first reported that TMR benefits were predicted by slow-oscillation phase at the time of cueing: cues played during one particular interval of the slow-wave cycle (180-270°) led to less forgetting of cued items than did cues played during other phases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps this rhythm entrained EEG oscillations in some participants, influencing slow-oscillation phase and delta power changes. Indeed, a recent study suggests that openloop auditory stimulation can induce slow-oscillation amplitude changes (Huwiler et al, 2022). Batterink et al (2016) first reported that TMR benefits were predicted by slow-oscillation phase at the time of cueing: cues played during one particular interval of the slow-wave cycle (180-270°) led to less forgetting of cued items than did cues played during other phases.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this rhythm entrained EEG oscillations in some participants, influencing slow‐oscillation phase and delta power changes. Indeed, a recent study suggests that open‐loop auditory stimulation can induce slow‐oscillation amplitude changes (Huwiler et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent study using TACS to target alpha oscillations reported a transient suppression of alpha power independent of the phase at which stimulation was applied 27 . Meanwhile, studies employing auditory stimulation in the same closed-loop manner have demonstrated that administering sounds at different phases of sleep's hallmark slow oscillation leads to different effects, such that sounds applied at the peak of slow oscillations increase its amplitude [28][29][30][31][32] (but see 33 ). In comparison to electrical stimulation, auditory stimulation offers several advantages, as it is inexpensive, easy to apply, has minimal side effects, and it does not cause artifacts on the electrophysiological (EEG) signal, thus permitting straightforward continuous monitoring of brain activity.…”
Section: Introductionmentioning
confidence: 99%
“…Closed-loop sensory stimulation has the potential to overcome this limitation, since sensory stimuli do not create artefacts in the EEG (allowing repeated neurophysiological interrogation), with the additional advantage of utilising safe, easy to apply and affordable technology. This approach has been used in sleep studies in which sounds are commonly phase-locked to the slow-oscillations (0.5-4Hz) of sleep [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation